Buying Behaviour of Herbal Cosmetics by Women Consumers : An Exploratory Study in Kolkata - Chattaraj, Dibyendu; Mazumder, Rabin; Lahiri, Sahana (Indian Journal of Marketing, 2018)
The market is witnessing a trend where consumers are shifting from the habits of purchasing and using chemical based or synthetic based cosmetics to herbal cosmetics. The present research paper was exploratory in nature and investigated the buying behaviour of women consumers on herbal cosmetics in Kolkata district of West Bengal. Herbal cosmetics are gaining popularity in the world, and India is not an exception to that. The Indian herbal cosmetics market is growing every year and hence, the competition between existing players is also in the upward direction. At the same time, various local brands are entering the Indian herbal cosmetics market. To sustain and peform in the competitive market, understanding the basic relationships between various demographic and socioeconomic factors of the consumers is important. The study was based on primary data captured through a structured questionnaire and was administered to a total of 187 respondents. Descriptive statistics were used to find out the significance of association between the demographic and socioeconomic attributes and frequency of buying herbal cosmetics. Factor analysis was considered appropriate to find out the factors underlying the buying behaviour of herbal cosmetics. The findings of the study showed a significant relationship between age, household income, and education with frequency of purchasing herbal cosmetics. The results suggested that Promotion, Attributes, Worth of Purchasing, and Demonstration Effect influenced the buying behaviour of herbal cosmetics.